Prevalence and influencing factors of osteoporosis among adults in Hebei province - Jing-jing ZHAO; Ya-jing CAO; Ji-xin SUN (Editorial Office of Chinese Journal of Public Health, 2022)
ObjectiveTo investigate the prevalence and influencing factors of osteoporosis among adults in Hebei province and to provide references for developing targeted osteoporosis prevention measures.MethodsA questionnaire survey and quantitative ultrasound bone density detection were conducted among 6195 permanent residents aged 20 - 80 years selected with multistage stratified cluster sampling in 7 districts or counties in Shijiazhuang, Chengde and Baoding city of Hebei province from July to September in 2017.ResultsAmong the participants, totally 89 osteoporosis cases were identified and the prevalence rate was 1.44%. Unconditional multivariate logistic regression analysis revealed that female gender and at older age were risk factors for osteoporosis; while, with an education of high school and above was a protective factor against osteoporosis.ConclusionThe prevalence of osteoporosis is relatively low and mainly influenced by gender, age and education level among adult residents in Hebei province.